2010
DOI: 10.1111/j.1540-4781.2009.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement Through FLES: A Case for Promoting Greater Access to Foreign Language Study Among Young Learners

Abstract: The No Child Left Behind Act of 2001 established foreign languages as a core curricular content area; however, instructional emphasis continues to be placed on curricular areas that factor into state educational accountability programs. The present study explored whether foreign language study of first‐year Grade 3 foreign language students who continued their foreign language study through Grade 5 in Louisiana public schools contributed to their academic achievement in curricular areas tested on the Iowa Test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Cooper et al () found that students who studied an FL in school outperformed students who did not on the SAT Reasoning Test, which is administered to secondary school–aged students. Early language learners (i.e., birth to age 8) also outperformed their monolingual peers in all areas (i.e., English language arts, math, science, and social studies) on the Iowa Test of Basic Skills and the Louisiana Educational Assessment Program for the 21st Century test in Taylor and Lafayette's () study. Adult bilingual learners performed better than their monolingual peers on the First Certificate of English test of reading comprehension in Modirkhamene's () study.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cooper et al () found that students who studied an FL in school outperformed students who did not on the SAT Reasoning Test, which is administered to secondary school–aged students. Early language learners (i.e., birth to age 8) also outperformed their monolingual peers in all areas (i.e., English language arts, math, science, and social studies) on the Iowa Test of Basic Skills and the Louisiana Educational Assessment Program for the 21st Century test in Taylor and Lafayette's () study. Adult bilingual learners performed better than their monolingual peers on the First Certificate of English test of reading comprehension in Modirkhamene's () study.…”
Section: Resultsmentioning
confidence: 94%
“…Garrett (2011) and Zaunbauer and Möller (2010) both found that bilingual children had higher math skills and achieved at a faster rate than their monolingual peers. The results of Taylor and Lafayette's (2010) U.S.-based research showed that FL/WL students outperformed their non-FL/WL counterparts on language achievement tests. Memory performance and recall were found to be an asset of bilinguals in the research of Bialystok and Feng (2009) and Kuska, Zaunbauer, and Möller (2010) when compared to their monolingual counterparts, thus suggesting the positive influence of FL/WL learning and bilingual education on higher academic achievement and performance.…”
Section: Higher Academic Achievementmentioning
confidence: 99%
“…The benefits propagated for moving early L2 learning into elementary schools or preschools are manifold. The increased exposure at this early age is expected to lead to linguistic benefits in terms of higher language proficiency and potentially more nativelike pronunciation (Flege & MacKay, ), advantages in academic achievement (Taylor & Lafayette, ), and intercultural advantages (Nikolov & Mihaljević Djigunović, ), as well as moderate advantages for phonological and morphosyntactic achievement (Larson‐Hall, ), which may, however, disappear quickly (Pfenninger, ). Furthermore, younger learners show fewer problems with language anxiety (Johnstone, ), higher levels of motivation and positive attitudes toward language learning (Börner, Engel, & Groot‐Wilken, ; Graham, Courtney, Tonkyn, & Marinis, ; Mihaljević Djigunović & Lopriore, ), and potentially better employability in the future.…”
Section: Early Foreign Language Learning: Brief Background and Researmentioning
confidence: 99%
“…9–10). Students in immersion learn content as well as or better than their peers who learn it in their L1 (e.g., Genesee, ; Taylor & Lafayette, ). Immersion students achieve high levels in L2 performance, although nonnative grammatical and discourse patterns persist (Harley, Cummins, Swain, & Allen, ; Swain, ).…”
Section: The Connections Goal Areamentioning
confidence: 99%